Close up on crystal plasticity - Mughrabi, Hael; Ungár, Tamas (Nature Materials, 2006)
A technique of X-ray diffraction was applied to investigate deformation-induced dislocation microstructures with submicrometer resolution. X-ray microscopy allows measurements of residual long-range internal stresses in deformed single crystals of copper with a spatial resolution of a few hundred nanometers. X-ray diffraction shows that long-range internal back-stresses prevailed in the cell interiors of their specimens that had been deformed in tension or in compression. The magnitude of the internal back-stresses varied from one cell interior to the next and shows that fluctuations are an inherent feature in deformed microstructures. The average diffraction profiles, obtained from large volumes of small crystal, exhibit characteristic asymmetrically broadened line profiles. The techniques provided advanced microstructural analysis of deformed crystalline materials.
Created from Fastlane, Scopus look-up